1977
DOI: 10.1126/science.887941
|View full text |Cite
|
Sign up to set email alerts
|

Neurogenesis in the Adult Rat: Electron Microscopic Analysis of Light Radioautographs

Abstract: Three-month-old rats were injected intraperitoneally with [3H]thymidine (4.3 microcuries per gram of body weight) and allowed to survive for 30 days. Radioautography of 1-micrometer sections revealed labeled cells in the granular layers of dentate gyrus and olfactory bulb; these were confirmed as neurons by electron microscopy of reembedded 1-micrometer sections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
651
2
11

Year Published

1996
1996
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,315 publications
(682 citation statements)
references
References 22 publications
11
651
2
11
Order By: Relevance
“…There are several niches in the adult brain in which NSCs persist throughout life and can respond to injurious processes [15][16][17][18]. New neurons are continuously generated in the anterior subventricular zone (SVZ) of adult rodents, from which they migrate via the rostral migratory stream to the olfactory bulb [19][20][21][22][23], and in the subgranular zone of the hippocampal dentate gyrus of both adult rodents [24][25][26][27] and humans [6,28]. The subependymal cell layer of the ventricles [29] and spinal cord [30] contains stem cells that give rise to both neurons and glia.…”
Section: Glial Progenitor Cells In the Adult Central Nervous Systemmentioning
confidence: 99%
“…There are several niches in the adult brain in which NSCs persist throughout life and can respond to injurious processes [15][16][17][18]. New neurons are continuously generated in the anterior subventricular zone (SVZ) of adult rodents, from which they migrate via the rostral migratory stream to the olfactory bulb [19][20][21][22][23], and in the subgranular zone of the hippocampal dentate gyrus of both adult rodents [24][25][26][27] and humans [6,28]. The subependymal cell layer of the ventricles [29] and spinal cord [30] contains stem cells that give rise to both neurons and glia.…”
Section: Glial Progenitor Cells In the Adult Central Nervous Systemmentioning
confidence: 99%
“…However, markers to distinguish among cell types were still not available at that time (Altman and Das, 1962, 1965, 1967Altman, 1966). The next landmark was achieved by Kaplan and colleagues when they presented evidence that labeled cells in the olfactory bulb and the dentate gyrus of adult rats had the ultrastructural characteristics of neurons, namely, synapses and dendrites (Kaplan and Hinds, 1977;Kaplan, 1984). This was followed by a set of elegant experiments in the 80s showing that songbirds generate new neurons that not only integrate into the brain and form synapses but were also functionally active able to respond to stimuli (Goldman and Nottebohm, 1983;Burd and Nottebohm, 1985).…”
Section: Will the Real Cns Stem Cell Please Stand Up?mentioning
confidence: 99%
“…This was followed by a set of elegant experiments in the 80s showing that songbirds generate new neurons that not only integrate into the brain and form synapses but were also functionally active able to respond to stimuli (Goldman and Nottebohm, 1983;Burd and Nottebohm, 1985). Since then, neurogenesis has been identified in at least three areas: hippocampus (Altman and Das, 1965;Kaplan and Hinds, 1977;Palmer et al, 1995;Taupin et al, 2000), olfactory bulb (Hinds, 1968;Kaplan and Hinds, 1977;Luskin, 1993;Okano et al, 1993;Lois and Alvarez-Buylla, 1994), and the nasal epithelium (Graziadei and Graziadei, 1979;Calof and Chikaraishi, 1989). Nevertheless, the exact location of CNS stem cells was not identified and it was not until 1999 that two groups, with conceptually different methods, localized the CNS stem cells to the periventricular zone in the brain: the ependymal cell (Johansson et al, 1999b) and the SVZ astrocyte (type B cells) (Doetsch et al, 1999).…”
Section: Will the Real Cns Stem Cell Please Stand Up?mentioning
confidence: 99%
“…These cells become incorporated into the gcl and express markers of mature granule neurons, including neuron specific enolase (NSE), the calcium binding protein calbindin, the NMDA receptor subunit NR1, and Neuronal Nuclei (NeuN): within 3 weeks of DNA synthesis (Cameron et al 1993a(Cameron et al , 1993bOkano et al 1993;Kuhn et al 1996). Cells produced in adulthood receive synaptic input and extend axons into the mossy fiber pathway (Kaplan and Hinds 1977;Kaplan and Bell 1984;Stanfield and Trice 1988). Recent studies have shown that this phenomenon is common to many species of mammals.…”
Section: The Production Of Hippocampal Granule Neurons Continues Intomentioning
confidence: 99%